Cost-Effectiveness of Peptide Enhanced Bone Graft i-Factor versus Use of Local Autologous Bone in Anterior Cervical Discectomy and Fusion Surgery - Thaci B; Yee R; Kim K; Vokshoor A; Johnson JP; Ament J (Dove Medical Press, 2021)
Bart Thaci,1 Randy Yee,2 Kee Kim,1 Amir Vokshoor,2- 4 J Patrick Johnson,5 Jared Ament2- 5 1University of California, Davis, Sacramento, CA, USA; 2Neuronomics LLC, Los Angeles, CA, USA; 3Neurosurgery & Spine Group, Los Angeles, CA, USA; 4Institute of Neuro Innovation, Santa Monica, CA, USA; 5Cedars Sinai Medical Center, Los Angeles, CA, USACorrespondence: Jared AmentNeuronomics LLC, 7320 Woodlake Ave, Suite 215, West Hills, CA, 91307, USATel +1 800 899 0101Fax +1 310 870 8677Email jared.ament@cshs.orgStudy Design: We conducted decision analytical modeling using a Markov model to determine the ICER of i-factor compared to autograft in ACDF surgery.Objective: The efficacy and safety of traditional anterior cervical discectomy and fusion (ACDF) surgery has improved with the introduction of new implants and compounds. Cost-effectiveness of these innovations remains an often-overlooked aspect of this effort. To evaluate the cost-effectiveness of i-FACTOR compared to autograft for patients undergoing ACDF surgery.Methods: The patient cohort was extracted from a prospective, multicenter randomized control trial (RCT) from twenty-two North American centers. Patients randomly received either autograft (N = 154) or i-Factor (N = 165). We analyzed various real-world scenarios, including inpatient and outpatient surgical settings as well as private versus public insurances. Two primary outcome measures were assessed: cost and utility. In the base-case analysis, both health and societal system costs were evaluated. Health-related utility outcome was expressed in quality-adjusted life years (QALYs). Cost-effectiveness was expressed as an incremental cost-effectiveness ratio (ICER).Results: In all scenarios, i-FACTOR reduced costs within the first year by 1.4% to 2.1%. The savings proved to be incremental over time, increasing to 3.7% over an extrapolated 10 years. The ICER at 90 days was $13,333 per QALY and became negative ("dominated") relative to the control group within one year and onwards. In a threshold sensitivity analysis, the cost of i-FACTOR could theoretically be increased 70-fold and still remain cost-effective.Conclusion: The novel i-FACTOR is not only cost-effective compared to autograft in ACDF surgery but is the dominant economic strategy.Keywords: cost-effectiveness, i-factor, spine fusion, spine allograft, cervical spondylosis, anterior cervical discectomy and fusion, cost analysis, decision analysis